Electronic Participation: Second IFIP WG 8.5 International Conference, ePart 2010, Lausanne, Switzerland, August 29 – September 2, 2010. Proceedings - Tambouris, Efthimios; Macintosh, Ann; Glassey, Olivier (Lecture Notes in Computer Science, 2010)
Book Front Matter of LNCS 6229